Penggunaan Media Dalam Pembelajaran PPKn di Prestige Bilingual School Kota Medan - Abdulgani Jamora Nasution; Jelita Dwi Septya; Fadhilah Uswah; Adinda Widyaningsih; Harri Gusnirwan (EduInovasi: Journal of Basic Educational Studies, 2023)
Education is an action that is carried out consciously and planned which aims to change the behavior of everyone. Departing from the problem of the education curriculum, various activities in the world of education and learning actually found studies that must be critically discussed in order to achieve the ideal goals of education. One that cannot be underestimated is the use of learning media. Based on the explanation above, the researcher is interested in carrying out a study entitled "Use of Media in Civics Learning at Prestige Bilingual School". Based on the title, background and formulation of the problem to be studied, the researcher uses descriptive qualitative methods. From the results of observations and interviews it has been found that Prestige Bilingual School is a school that is aware of the importance of using instructional media to increase students' understanding of each material being taught. The learning media used at this school in teaching PPKn materials are projectors, art and craft, assemblies to IPS-PKN Week. Keywords: PPKn, learning media, Prestige Bilingual School